Strategy, strategic alignment, and the market environment: a case study of CE Turner - Mcgrath, Joseph (2015)
Although the link between strategy and capabilities has been studied extensively, for the most part, this research has focused on the application of one specific internal or external strategic viewpoint. Using a case study method, this research applies a holistic analysis taking into account all strands of strategic management literature. CE Turner a precision engineering firm located in the east midlands is analysed within this research. The results of the study indicate that CE Turner has taken positive actions towards aligning their strategic objectives with their current capabilities. However, contrary to expectations, this alignment may not be enough to set the firm apart form competition due to the underlying market structure.